Antibiotics and priority effects on colonizing resistant Escherichia coli strain assemblages in a community setting - Eric Ng’eno (PLoS ONE, 2026)
Colonizing antibiotic resistant bacteria often exists within functionally structured microbial communities, where occurrence is influenced by dependencies essential to stability and function. Considering these interactions could improve understanding of factors influencing diversity of colonizing resistant bacteria within human community settings. Using a framework that considered biotic interactions, we reexamined factors associated with assemblage of colonizing antibiotic resistant Escherichia coli strains in a densely populated urban informal settlement. We identified antibiotic selection, colonization legacy, positive feedbacks and dispersal as key assembly processes. Antibiotics and colonization legacy exerted strain-specific effects while dispersal factors influenced all strains rather uniformly. Specifically, areas frequently exposed to bactericidal antibiotics were dominated by locally established resistant strains, whereas areas frequently exposed to bacteriostatic antibiotics had increased presence of less-established strains. Assemblage configuration was influenced by relative abundance of strains initially present in and around the disturbed areas. Hygiene practices reinforced local strains consistently while weather variables had variable effects: high monthly average minimum temperatures increased abundance of nearly all strains, whereas increases in monthly average maximum temperature, humidity, and rainfall uniformly decreased strain abundance. Overall, we show that survival selection, driven by selective forces, and dispersal selection, shaped by colonization potential, jointly influenced strains recruitment and assembly, suggesting antibiotics and priority effects as factors contributing to resistant E. coli assemblages in this setting. Together these findings underscore need for context-specific antibiotic stewardship and hygiene interventions.